Systematic literature review on emotion recognition AI feedback in mathematics game online among middle school students - Razid Ananda Siregar; Rahmah Johar; Mailizar (Universitas Islam Negeri (UIN) Mataram, 2026)
[English]: This study synthesizes, critically analyzes, and maps empirical evidence regarding the effectiveness of artificial intelligence (AI) feedback in emotion recognition within online mathematics games among middle school students. Employing the Systematic Literature Review (SLR) method, this research utilized the PRISMA 2020 guidelines. A rigorous screening process of 495 articles from EBSCO, Springer Nature, and Taylor & Francis databases resulted in 20 final inclusion articles. The synthesis findings reveal a research shift toward feedback designs that deliberately influence the user’s emotional state, dominated by emotion-based feedback and delivery method-based feedback. The impact of this feedback is positive, specifically improving mood and well-being and facilitating direct emotional regulation. The effectiveness is moderated by three main factors: system and technology design, cognitive and behavioral factors, and content and learning situations. These findings imply that online game designers must consider system architectures that actively manage students’ emotional states through social support and adaptive content, beyond just providing performance feedback. Since the reviewed literatures are dominated by quantitative research, this study recommends that future research incorporates qualitative approaches to more deeply explore the nuanced, subjective emotional experiences of students interacting with AI systems. [Bahasa]: Penelitian ini mensintesis, menganalisis secara kritis, dan memetakan bukti empiris mengenai efektivitas umpan balik kecerdasan buatan (AI) dalam pengenalan emosi pada permainan matematika daring di kalangan siswa sekolah menengah. Menggunakan metode Systematic Literature Review (SLR), penelitian ini mengikuti pedoman PRISMA 2020. Proses penyaringan yang ketat terhadap 495 artikel dari basis data EBSCO, Springer Nature, dan Taylor & Francis menghasilkan 20 artikel yang memenuhi kriteria inklusi. Temuan sintesis menunjukkan adanya pergeseran tren penelitian menuju desain umpan balik yang secara sengaja memengaruhi keadaan emosional pengguna, yang didominasi oleh umpan balik berbasis emosi dan umpan balik berbasis metode penyampaian. Dampak dari umpan balik ini bersifat positif, khususnya dalam meningkatkan suasana hati dan kesejahteraan, serta memfasilitasi regulasi emosi secara langsung. Efektivitas tersebut dimoderasi oleh tiga faktor utama: desain sistem dan teknologi, faktor kognitif dan perilaku, serta konten dan situasi pembelajaran. Temuan ini menyiratkan bahwa perancang permainan daring harus mempertimbangkan arsitektur sistem yang secara aktif mengelola keadaan emosional siswa melalui dukungan sosial dan konten adaptif, lebih dari sekadar memberikan umpan balik performa. Karena literatur yang ditinjau didominasi oleh kajian kuantitatif, penelitian ini merekomendasikan agar studi di masa depan menggabungkan pendekatan kualitatif untuk mengeksplorasi pengalaman emosional subjektif siswa yang lebih bernuansa saat berinteraksi dengan AI.